The Role of Management in Guest Complaint Handling at Seleriana Restaurant, The Kana Kuta Hotel, Bali - Riska Kristiani; Ida Ayu Putu Sulastri; I Nengah Sandi Artha Putra (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
Guest complaints in hotel restaurants are important managerial signals because they reflect gaps between expected service and actual guest experience. This study aims to analyze the role of management in handling guest complaints at Seleriana Restaurant, The Kana Kuta Hotel, Bali; identify operational constraints; and formulate improvement efforts for complaint handling in food and beverage service. This study applied a descriptive qualitative approach using document review, non-participant observation, semi-structured interviews, and online guest review analysis from Google Review and Tripadvisor. The data were analyzed thematically by grouping complaint patterns, management roles, operational constraints, and corrective actions. The findings indicate that guest complaints at Seleriana Restaurant are mainly related to menu variety, service speed, order accuracy, table clearing, staff responsiveness, communication, and perceived fairness in service attention. Management plays a central role through four managerial functions: planning complaint-handling procedures, organizing escalation channels among service staff, kitchen, cashier, supervisor, and restaurant manager, actuating staff through briefing and service recovery training, and controlling recurring complaints through complaint logs and evaluation. The main constraints include inconsistent service coordination, limited staff empowerment, uneven complaint documentation, and the absence of a fully operational complaint-handling flow. The study recommends a more practical complaint-handling SOP, LEARN/HEAT-based service recovery training, clearer authority limits for frontline staff, systematic complaint recording, and specific managerial responses to online reviews. The findings confirm that guest complaints should be treated not only as service problems but also as continuous service-quality improvement mechanisms in hotel restaurant operations.